A intensificação do sofrimento psíquico na pandemia: implicações para o processo de medicalização e da produção de subjetividade no campo da atenção básica - Lima, Wany Teixeira (2023)
The aim of this paper was to analyze the discourses and practices of the medical device in the pandemic facing mental health demands in the context of primary care. The research was based on documents such as scientific articles, dissertations, theses and other references published in databases, and the analysis was carried out using Foucault's genealogical historical perspective. In this research, two main sections have been developed, which were divided into two phases: 1) contemporary: mapping the normalizing function of the medical device in the pandemic in its disciplinary and control practices; 2) genealogical section between the 18th and 19th centuries: mapping and contextualizing the historical forces that cross the device in question to see how its developments converge in lines of knowledge, power and subjectivation in the contemporary. As a result, we found normalizing practices under the binary of normal versus pathological, presenting themselves as a phenomenon of medicalization, problematizing the place of psychology in relation to the processes presented, understanding new paradigms about scientific truth and the effects resulting from it.